Multi-party semi-quantum key distribution protocol based on hyperentangled Bell states - Tian, Yuan; Li, Jian; Ye, Chongqiang; Li, Chaoyang (Frontiers in Physics, 2022)
Semi-quantum key distribution allows generating a raw key among two communication participants. In which a sender is a quantum participant, and a receiver is a classical participant. This paper presents an original semi-quantum key distribution protocol based on hyperentangled Bell states. The hyperentangled Bell states can be entangled simultaneously in polarization and spatial degrees of freedom, enhancing channel capacity. According to the characteristic of hyperentangled Bell states, the proposed protocol is more efficient than the protocol based on Bell states. Moreover, the measure-resend attack, the intercept-resend attack and the entangle-measure attack are analyzed in detail. The security analysis demonstrates that the proposed protocol is secure. Besides, a multi-party semi-quantum key distribution scheme based on hyperentangled Bell States is proposed, which can realize key distribution between one quantum participant and multiple classical participants.